Draft Annual Plan 1989-90 Review and Outline Volume-I Government of Manipur - Planning Commission (Planning Commission, 1989)
Allocation under I.R.D.P. In 1987-88 was married under the formula of 2/3 weightage to incidence of poverty and 1/3rd according to the number of blocks as existed at the end of the Sixth Plan. The formula has been changed in 1988-89 to 75% weightage to incidence of poverty and 25% on the basis of uniformity. Against the target of 87,000 beneficiaries, the state had covered 27, 637 beneficiaries until 1987-86, which includes 332 Scheduled Caste and 19,039 Scheduled tribe beneficiaries.
Government of Manipur, Planning Department